A three-step system for creating training and competition loads in the sport of wrestling - Bekmuratov Keunimjay Turimbetovich (Genius Publishing Group, 2022)
The paper considers approaches to automating the construction of training plans of athletes for the sport of kurash, as well as analysis of plans training and competition with the help of specially designed programs. The data of the research work on the macro -structure and mesostructure of the training of athletes in sports in kurash are given.
Keywords: Macrocycle; mesocyclle; plan; training; analysis